Analisis Penjadwalan Produksi Berdasarkan Pesanan Menggunakan Metode Asas Prioritas pada CV Davero Cemerlang Indonesia Surabaya - Moh. Fahrul Faris; Wiwik Handayani (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2022)
The purpose of this study was to determine the most efficient order scheduling technique on CV. Davero Jaya Shining Indonesia to reduce delays in order fulfillment. The suggested scheduling approach is based on a priority rule system that includes the following criteria: first come, first served, lowest processing time, longest processing time, and earliest due date (first come first served). Davero Jaya Cemerlang Indonesia uses the SPT technique in its manufacturing process, according to their company CV. The company decided to adopt this technique because it seemed reasonable from a consumer's point of view. The downside of this technique is that it often causes delays in completing client orders. Based on the results of data analysis and debates that have been given, the FCFS technique is the most superior method among others. Considering the fact that the findings of the FCFS method effectiveness measure are consistent with the current criteria, which include minimum average completion scores, maximum utility, minimum average delay, and minimum average labor force in the system. Therefore, the researchers gave suggestions to the company CV. Davero Jaya Cemerlang Indonesia to use the FCFS method as an alternative production scheduling method. With the application of the FCFS method in CV. Davero Jaya Cemerlang Indonesia is expected to be able to help resolve production scheduling problems that have been happening so far. So that the problem of delays in completing orders can be minimized. Keywords: Scheduling, Gantt Chart, Priority Principles and CV. Davero Jaya Cemerlang Indonesia